DICTION ANALYSIS IN MAKING EMPATHETIC RESPONSES FOR DIABETIC OF NURSING STUDENT IN STIKES BINA USADA BALI - Si Putu Agung Ayu Pertiwi Dewi; Ni Komang Purwaningsih; Ni Putu Lindawati (LITERA : Jurnal Bahasa Dan Sastra, 2017)
ABSTRACTEnglish for specific purposes is useful to be used in some sectors like tourism, hospital, law,and so on. In STIKES Bina Usada Bali especially, the students as the second language learnermay face some errors during learning how to use the correct English expression. They hardlychoose the correct word or expression when they try to speak to the patient in makingempathetic responses especially for diabetic. This study aimed at describing diction byidentifying meaning and supporting element context and the implication toward Englishlearning especially in making empathetic responses for diabetic of nursing student of StikesBina Usada Bali. This research used the descriptive qualitative method. In the form of researchword used in making empathetic responses for diabetic when the student do speaking activity.Data analysis based on the use of word meaning denotation and connotation context.Keywords: diction, speaking, empathetic responses, diabeticABSTRAKEnglish for Spesific Purposes berguna untuk digunakan di beberapa sektor seperti pariwisata,rumah sakit, hukum, dan sebagainya. Di STIKES Bina Usada Bali khususnya, siswa sebagaipelajar bahasa kedua mungkin menghadapi beberapa kesalahan selama belajar bagaimanamenggunakan ekspresi bahasa Inggris yang benar. Mereka tidak memilih kata atau ungkapanyang benar saat mereka mencoba berbicara kepada pasien dalam membuat respons empatiterutama untuk penderita diabetes. Penelitian ini bertujuan untuk mendeskripsikan diksi denganmengidentifikasi makna dan elemen pendukung dan implikasinya terhadap pembelajaranbahasa Inggris terutama dalam membuat tanggapan empati untuk penderita diabetes pada siswaKeperawatan Bina Usada Bali. Penelitian ini menggunakan metode deskriptif kualitatif. Dalambentuk kata penelitian yang digunakan dalam membuat respons empati untuk penderitadiabetes saat siswa melakukan aktivitas berbicara. Analisis data didasarkan pada penggunaankata yang berarti denotasi dan konotasi konteks.Kata kunci: diksi, berbicara, respon empati, diabetes